Epilogue: Moral Panics and Body Cameras - Wasserman, Howard M. (2015)
This brief follow-up to Moral Panics and Body Cameras comments on the weeks after that essay was published and what those events show about the efficacy of body cameras and video evidence as a response to police-public conflicts